Four Pillars of Sharia Microfinance Institution Development: Empat Pilar Pengembangan Lembaga Keuangan Mikro Syariah - Dayu Rizki Nurhamda; Saparuddin Siregar; Muhammad Ikhsan Harahap (Academia Open, 2025)
General Background: Lembaga Keuangan Mikro Syariah (LKMS) plays a crucial role in promoting inclusive finance and supporting small-scale economic empowerment within Islamic economic systems. Specific Background: Despite the growth of more than 500 LKMS in Indonesia, challenges remain regarding competition with conventional institutions, limited capital, regulatory gaps, low financial literacy, and adaptation to digitalization. Knowledge Gap: Previous studies have examined governance, literacy, and digitalization issues in LKMS, but limited research has integrated theoretical insights with practical challenges through the perspective of Prof. Dian Masyita, a leading scholar in Islamic microfinance. Aims: This study analyzes the development strategies of LKMS based on Prof. Dian Masyita’s thought, focusing on sustainability, inclusivity, and innovation. Results: Findings highlight four pillars for strengthening LKMS: community-based approaches, reinforcement of Sharia-compliant business models, product diversification, and technological utilization. LKMS is not only a financial institution but also a social agent fostering justice, transparency, and local empowerment. Novelty: The research identifies unique strategic patterns by linking theory with field realities, extending beyond prior literature. Implications: Strengthening LKMS through these pillars can enhance financial inclusion, reduce poverty, and promote sustainable socio-economic development, while offering guidance for policymakers and practitioners in advancing Islamic finance.Highlight : LKMS supports Islamic financial inclusion and community welfare. Four main pillars: community, Islamic business model, product diversification, technology. Main challenges: competition with fintech, regulation, and low financial literacy. Keywords : Sharia Microfinance Institutions, Financial Inclusion, Sharia Economic Development, Financial Literacy, Technology